What are the key endodontic factors associated with oral health–related quality of life?. (25th June 2013) - Liu, P.; McGrath, C.; Cheung, G.
Abstract Aim To determine the associations between endodontic factors and oral health–related quality of life (OHQoL), controlling for socio‐demographics, pain and other oral health clinical factors. Methodology OHQoL assessments were conducted amongst a consecutive sample of 412 Chinese patients requiring endodontic treatment employing the short‐form Oral Heath Impact Profile (OHIP‐14). Information on (i) number of teeth requiring endodontic treatment, (ii) tooth type, (iii) retreatment requirements, (iv) periapical radiolucency assessment and (v) diagnostic classification was obtained. In addition, socio‐demographic information (age, gender, educational attainment and family income), pain ratings on a visual analogue scale (VAS) and other clinical oral health status information were collected. Results Bivariate analyses identified association between number of teeth requiring endodontic treatment and summary OHIP‐14 score (P < 0.01) and four of its seven domain scores (P < 0.05). Need for endodontic retreatment was associated with summary OHIP‐14 score (P < 0.05) and two of its seven domain scores (P < 0.05). In regression analyses having controlled for socio‐demographics, other clinical factors and pain rating amongst 15 confounding variables, patients requiring endodontic treatment for multiple teeth were more than twice as likely to have poor OHQoL (upper quintile OHIP‐14 scores) compared with those requiring endodontic treatment for a single tooth (OR = 2.16, 95% CI 1.17, 3.98, P < 0.05). Pain VAS rating and age also emerged as significant factors associated with poor OHQoL in the regression analysis. Conclusion OHQoL is compromised amongst patients requiring endodontic treatment. Number of teeth requiring endodontic treatment is associated with poor OHQoL, controlling for socio‐demographic and other oral health clinical and pain factors.